Trends and disparities in subjective upward mobility since 1940 - Berger, T; Engzell, P (SAGE Publications, 2020)
Concerns that prospects for upward mobility are fading are common in popular and scientific discourse. The fact that fewer Americans today surpass their parents’ economic status than in the past has been invoked to explain trends ranging from the recent spike in drug and alcohol poisonings to the growing appeal of right-wing populism. Using General Social Survey data, the authors ask whether people actually feel that their standard of living is falling short of that of previous generations. In contrast to data on income, education, or occupation, a majority still perceive that they have attained a higher standard of living than their parents. At the same time, mobility experiences are becoming increasingly polarized: subjective upward mobility is rising among highly educated, minority, and urban populations and declining among less educated and rural populations.